DINAMIKA TIM KERJA DALAM MENGHADAPI DISRUPSI ARTIFICIAL INTELLIGENCE: SYSTEMATIC LITERATURE REVIEW (SLR) - Nursyifa Salsabila Rahmadani Manik; Syalwah Ilmiah Nadifah; Azzahra Indra Wijaya; Lely Nur Azizah; Ni Wayan Sukmawati Puspitadewi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
This study examines the impact of Artificial Intelligence (AI) on team dynamics in organizational settings, particularly in communication, collaboration, and trust. The rapid development of AI has transformed work systems, yet its influence on team interaction remains underexplored. This research aims to analyze how AI implementation affects team dynamics using a Systematic Literature Review (SLR) approach guided by the PRISMA framework. The research instruments include inclusion–exclusion criteria and thematic synthesis, with 19 peer-reviewed journal articles (2021–2025) from Scopus and Google Scholar as the research subjects. The findings reveal that AI enhances team performance through improved efficiency, faster data processing, and data-driven decision-making, while also supporting more structured communication and collaboration. However, challenges such as miscommunication and limitations in understanding socio-emotional context persist. Trust is identified as a key factor influencing effective human–AI collaboration. In conclusion, the success of AI integration depends not only on technological capability but also on human, psychological, and organizational factors.